Nepafenac: An Ophthalmic Nonsteroidal Antiinflammatory Drug for Pain After Cataract Surgery. (June 2013) - Jones, Benjamin M; Neville, Michael W
OBJECTIVE: To examine the efficacy of nepafenac in the treatment of pain and inflammation in patients after cataract surgery using evidence from controlled clinical studies. DATA SOURCES: Citations in Google Scholar, PubMed, and Web of Science from January 1, 2005, to March 25, 2013, were identified using nepafenac and cataract as search terms. STUDY SELECTION AND DATA EXTRACTION: The literature search was limited to human studies published in English. Three trials that compared nepafenac with other nonsteroidal antiinflammatory drugs (NSAIDs) were included. DATA SYNTHESIS: The pharmacokinetics and pharmacodynamics of nepafenac 0.1% suspension (and its active metabolite, amfenac) were compared with bromfenac 0.09% solution and ketorolac 0.4% solution with respect to aqueous humor concentrations and ability to reduce cyclooxygenase 1 and 2 (COX-1 and COX-2) enzymes. The maximum concentration (Cmax ) values of ketorolac and amfenac were statistically similar, while the Cmax of bromfenac was significantly lower than that of amfenac. Ketorolac most effectively inhibited COX-1 enzymes; COX-2 enzymes were most effectively reduced by amfenac. When nepafenac 0.1% suspension was compared with placebo and ketorolac 0.5% solution, nepafenac achieved a higher percentage cure rate than placebo at day 14 (p = 0.0241). Significant differences in cure rates between nepafenac and ketorolac were not observed. Nepafenac 0.1%, bromfenac 0.09%, and ketorolac 0.45% were compared to determine which most effectively reduced prostaglandin E2 (PGE2 ) following surgery. PGE2 concentrations were significantly lowest in the ketorolac group, followed by the bromfenac and nepafenac groups, respectively. Topical nepafenac 0.1% suspension was approved in 2005. A 0.3% suspension was approved in October 2012. The 0.3% product may have some advantages over its predecessor: it is dosed once rather than thrice daily, which may increase patient adherence and improve outcomes. The price and dosing frequency of the 0.3% product are comparable to those of bromfenac 0.09% solution. CONCLUSIONS: The 2 nepafenac products appear to be equally efficacious, with a slightly increased adverse event rate in patients using the 0.3% versus 0.1% formulation. Head-to-head clinical trials that compare the 0.3% product with the 0.1% product or other commercially available NSAIDs are unavailable.